2019
DOI: 10.1111/vsu.13242
|View full text |Cite
|
Sign up to set email alerts
|

Single‐port laparoscopic‐assisted ovariohysterectomy with a modified glove‐port technique in dogs

Abstract: Objective To describe a single‐port laparoscopic‐assisted ovariohysterectomy (LOHE) with a modified glove‐port technique in dogs and compare it with previously published laparoscopic techniques for LOHE in dogs. Study design Prospective clinical study and technique description. Animals Forty‐two healthy female dogs. Methods Laparoscopic‐assisted ovariohysterectomy was performed with a custom‐made single‐port device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(249 reference statements)
1
9
0
Order By: Relevance
“…Another advantage of the use of SILS was the possibility to suspend pneumoperitoneum and laparoscopic abdominal exploration, performing the rest of the surgical intervention extracorporeally. This ability was particularly appreciated during the GI tract surgery (i.e., enterectomy and enterotomy) [ 14 , 39 , 50 ] or uterus ligation during OVH [ 19 , 34 , 37 ] and Pyometra [ 15 , 24 , 26 ]. The combination of a WR and SILS port, or other systems that combine the removal of the cap with the instrument portal platform of WR, was particularly helpful for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of the use of SILS was the possibility to suspend pneumoperitoneum and laparoscopic abdominal exploration, performing the rest of the surgical intervention extracorporeally. This ability was particularly appreciated during the GI tract surgery (i.e., enterectomy and enterotomy) [ 14 , 39 , 50 ] or uterus ligation during OVH [ 19 , 34 , 37 ] and Pyometra [ 15 , 24 , 26 ]. The combination of a WR and SILS port, or other systems that combine the removal of the cap with the instrument portal platform of WR, was particularly helpful for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we evaluated the surgical method, operative time, safety, and usefulness of 3‐port LOHE using an ultrasonic coagulation and incision device in dogs <5 kg. Many published papers document the operative time and procedure of LOHE, 1,4,7,12,13 but no reports on LOHE using 3 ports and ultrasonic coagulation and incision devices in dogs <5 kg seem to be available. A study using 3 ports and a harmonic scalpel in a 10–12 kg dog with LOHE reported an operative time of 55 min 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The glove port is an improvised single-incision port consisting of an O-ring abdominal retractor (Alexis O Wound Retractor; Applied Medical, Rancho Santa Margarita, CA, USA) and a surgical glove. The port is assembled as previously described [ 10 ]. To achieve comparable results, the same 5-mm SILS cannulas were used to assemble the glove port.…”
Section: Methodsmentioning
confidence: 99%
“…A cost-effective alternative to commercial SPASs was described using an adjustable O-ring retractor and a surgical glove [ 8 ]. Recently, this technique was successfully used to conduct an ovariohysterectomy in a dog treated for pyometra [ 9 , 10 ]. Furthermore, the duration of surgery using a homemade glove port was shorter than other single-incision laparoscopy techniques, or multi-port laparoscopy, when used on normal uteri [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation